Exploring new technologies for the future generation: exploration–exploitation trade-off in an intergenerational framework - Nakawake, Y; Kobayashi, Y (The Royal Society, 2024)
Decision making on exploring or exploiting technology was studied by means of a laboratory experiment with a two-generation framework. In this framework, the design of a virtual tool is transmitted from the first to second generation, and hence, the former can help the latter by frequently exploring better tool designs but at the cost of reduced opportunities to exploit the existing tool to increase its own benefits. We set two experimental conditions (‘repaid’ and ‘unrepaid’) as well as a control condition (asocial), in which the second generation is absent. In the ‘repaid’ experimental condition, participants received an extra payment proportional to the score gained by the second generation, such that they were monetarily incentivized to help the second generation. Such an incentive was not given in the ‘unrepaid’ condition. An analysis of a formal model and computer simulations predicted that rational participants should increase investment in exploration only in the repaid condition when compared with the asocial control. The prediction was confirmed by the results of the experiment. These findings together suggest that humans may not have a propensity to invest in costly exploration of new technologies solely to help future generations.